La diversidad de las diversidades. Reflexiones sobre el pluralismo cultural en América Latina - Bartolomé Bistoletti, Miguel Alberto (Comparative Cultural Studies: European and Latin American Perspectives, 2016)
This analytical essay argues that the issue of ethnicity in Latin America is not an appeal to the past, but an important component of social thought and contemporary politics. A brief historical approach suggests that Latin American states were formed as uninational political apparatus on ethnic configurations, highlighting the cultural repression and ethnic domination are an integral part of its state design. The essay realizes that the poverty of ethnic groups is not accidental, as it represents the result of a specific historical project. It also discusses the current existence of multiple cultural predicates allocable to liberal and individualistic concept of citizenship.